(3CSQGQ GdNGajIs - (3TGehQ gfQjs
(3ChdgG (B:s
(3gPG cJGH ajg SQGddg GdCYXe s
(3BNQgG (B:s
(3hGdLfhHjI gi GdMQha GdJQCHjI hGddg GYde s
(3Vef eLehY , JQJjHgG (B: (3GdYGTQs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3JHUQGJ GdCUd (B:s
(3HgG NQe s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs